Aplicación didáctica de la balanza "pesaoro" de Arquímedes - Salvat Altés, A.; Sánchez Real, José (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this article two methods are exposed —with its practical application in the school— in order to discover whether the golden crown of King Illeron III from Siracusa (III c. bC) was totally made of gold or, on the contrary, the goldsmith who had made it, changed by silver part of the gold given by the King.